Pengaruh Permainan Playdough Terhadap Kreativitas Anak Kelompok B Di Tk Pertiwi 2 Kahuman Polanharjo Klaten Tahun 2016 - Friyani Vanni, Astida; Dr. Darsinah,, M.Si; Wili Astuti, S.Pd,M.Hum (2017)
ABSTRACK Astida Friyani Vanni/A520120078. THE INFLUENCE OF PLAYDOUGH GAME TO THE CHILDREN'S CREATIVITY GROUP B ON TK PERTIWI 2 KAHUMAN POLANHARJO KLATEN IN YEAR 2016. Thesis. Faculty of teacher training and educational sciences. University of Muhammadiyah Surakarta. April, 2017. The purpose of this research is to know the influence of playdough game to the children's creativity of Group B in TK Pertiwi 2 Kahuman Polanharjo Klaten in 2016. This reserach is one group pretest-posttest experimental design. The subject of this research are the children of Group B TK Pertiwi 2 Kahuman totalling 10 children. Data on children's creativity was collected through observation method. Data analysis technique used was t-test. The result of data analysis was value of tcount < - t table = - 19,243 < -1,833, hence Ho was denied and Ha was supported. The conclusion of this research is influence was found in the relationship between playdough game and the creativity of children Group B on TK Pertiwi 2 Kahuman Polanharjo Klaten in 2016. Keywords: playdough, creativity.